How Government Experts Self-Sabotage The Language of the Rebuffed - Gerblinger, Christiane (ANU Press, 2022)
After official policy advice to governments is publicly released, governments are often accused of ignoring or rejecting their experts. Commonly represented as politicisation, this depiction is superficial. Digging deeper, is there something about the official advice itself that makes it easy to ignore? Instead of lamenting a demise of expertise, Christiane Gerblinger asks: does the expert advice of policy officials feature characteristics that invite its government audience to overlook or misread it? To answer this question, Gerblinger critically examines official policy advice and finds the language of the rebuffed: government experts reluctant to disclose what they know so as to accommodate political circumstances. She argues that this language evades stable meaning and diminishes the democratic right of citizens to scrutinise the work of government.